1988
DOI: 10.1093/jee/81.4.1226
|View full text |Cite
|
Sign up to set email alerts
|

Repellent and Growth-Inhibiting Effects of Turmeric Oil, Sweetflag Oil, Neem Oil, and “Margosan-O” on Red Flour Beetle (Coleoptera: Tenebrionidae)

Abstract: In a food preference chamber, fewer adults of red flour beetle (Tribolium castaneum Herbst) settled in rice grain treated with 100, 500, or 1,000 ppm of the oil of turmeric Curcuma longa (L.), sweetflag Acarus calamus (L.), or neem Azadirachta indica A. Juss, or "Margosan-O" (a commercial neem-based insecticide). Repellency increased with increasing concentrations of the oils and Margosan. In another choice test, filter paper strips treated with turmeric oil or sweetflag oil at 200, 400, or 800 JLg/cm 2 repell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 6 publications
5
41
2
1
Order By: Relevance
“…After each test the "Y" glass tube and the gas washing bottles were washed with water, rinsed with acetone and dried at 80 o C for 1h. Each treatment was replicated four times and percentage repellency (PR) values were computed using the methods of Jilani et al (1988) as:…”
Section: Repellency Bioassaymentioning
confidence: 99%
“…After each test the "Y" glass tube and the gas washing bottles were washed with water, rinsed with acetone and dried at 80 o C for 1h. Each treatment was replicated four times and percentage repellency (PR) values were computed using the methods of Jilani et al (1988) as:…”
Section: Repellency Bioassaymentioning
confidence: 99%
“…Liu and Ho (1999) reported that essential oil of cardamom was more repellent to T. castaneum (Herbst) than to S. zeamais (Motsch). Jilani et al (1988) found that extract of neem leaves and seeds (5 g L -1 ) repelled T. castaneum. Elhag (2000) pointed out that the highest repellency of C. maculatus was found in R. stricta leaves (82.0%), A. indica seeds (76.8%), H. bacciferum aerial parts (59.2%) and citrus peels (58.6%).…”
Section: Discussionmentioning
confidence: 94%
“…Plant products have several uses in insect control. These products have also been studied for acute toxicity, antifeedant, or repellent, attractant, and fumigant effects, as well as inhibiting reproduction of many pest species [3; 4], products from several floral species have been demonstrated to act as repellents, toxicants and antifeedants against a number of Coleoptera that attack stored products [5] conducted insect repellency assay using extracts of different plants on stored product pests. Oils of many plants have also been reported as repellent and toxic chemicals for the management of stored grain insect pests [6].…”
Section: Introductionmentioning
confidence: 99%